THE EFFECT OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. ADI KARYA - Hayanuddin Safri; Zuriani Ritonga; Rahmi Rahmi; Sufitrayati Sufitrayati; Nelly Nelly (SEAN Institute, 2022)
PT Adi Karya is a company engaged in the contractor sector, which requires the expertise and ability of employees to be able to operate every task assigned by the company to its employees. With the intensity of the work being carried out, PT Adi Karya always wants its employees to have high motivation and satisfaction with the work done so that performance will increase. In accordance with the description above, the authors feel interested in conducting research entitled: